A new peroxidase from the roots of the Algerian white turnip (Brassica rapa, variety rapa): extraction, purification, characterisation, and antioxidant potential. Issue 6 (2nd November 2022) - Dahdouh, Amel; Boucherba, Nawel; Bouacem, Khelifa; Mechri, Sondes; Amirouche, Adel; Aksas, Ali; Jaouadi, Bassem; Kati, Djamel Edine
Abstract: Due to its various biological activities, the roots of Brassica rapa (turnip), has been applied as a therapeutic agent in traditional medicine. The current study aimed to purify a plant peroxidase (POD; designated as TRP) from Algerian white turnip ( B. rapa, variety rapa ) roots, to homogeneity and to characterise it biochemically. The molecular weight of the purified TRP was determined to be ∼58 kDa as estimated by sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) and high-performance liquid chromatography (HPLC). The TRP Reinheitzahl values (RZ) and specific activity were 2.9 and 14, 500 U/mg, respectively. Its N-terminal sequence exhibited high identity with those of class III-PODs. TRP showed optimal activity at 55 °C and pH 6 (guaiacol), was completely inhibited by sodium azide (NaN3 ) and potassium cyanide (KCN) and exhibited greater catalytic efficiency than that of the well-known horseradish peroxidase (HRP) from Armoracia rusticana . TRP demonstrated antioxidant activities with 45% and 61.49% of 2, 2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS ) and hydroxyl ( OH) radical scavenging, respectively, as well as ferrous ion chelating (52.96%) and reducing (48.32%) powers. This study provides information regarding the potential role of TRP in enzyme therapy (as applied in the pharmaceutical and medicinal industries), with biological eradication of free radicals.